Volume 2: Combustion, Fuels and Emissions, Parts a and B 2011
DOI: 10.1115/gt2011-45125
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Operational Window of a Swirl Stabilized Syngas Burner Under Atmospheric and High Pressure Conditions

Abstract: Providing better fuel flexibility for future gas turbine generations is a challenge as the fuel range is expected to become significantly wider (natural gas, syngas, etc.). The technical problem is to reach a wide operational window, regarding both operational safety and low emissions. In a previous paper an approach to meet these requirements has already been presented. However, in this previous study it was difficult to exactly quantify the improvement in operational safety due to the fact that the flashback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Among the important results obtained in these experiments is the conclusion that the critical velocity gradients at the wall required to avoid wall boundary layer flashback increase steeply as the pressure increases (Mayer et al 2011).…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the important results obtained in these experiments is the conclusion that the critical velocity gradients at the wall required to avoid wall boundary layer flashback increase steeply as the pressure increases (Mayer et al 2011).…”
Section: Previous Workmentioning
confidence: 99%
“…While boundary layer flashback has previously represented a minor issue for natural gas fired gas turbines, mounting evidence involving premixed combustion of hydrogen-rich syngas at gas turbine conditions (high pressure, high reactants' temperature) indicates that boundary layer flashback may constitute a key challenge (Mayer et al 2011) even in the presence of large quantities of diluent (Carroni 2006). …”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most serious operability issues often preventing modern combustors from operating in a safe, efficient, and reliable manner is flashback when the flame propagates upstream of the design position, where it is supposed to stabilize, and into the premixing duct [3]. Common flashback mechanisms include propagation of the turbulent flame in the core flow of the premixer duct or in its wall boundary layers, oscillations of the flame location due to combustion instabilities or combustion induced vortex breakdown [5]. Regardless of the initiating cause of flashback, once flashback occurs the flame will ultimately reach the fuel injection nozzles.…”
Section: Introductionmentioning
confidence: 99%
“…Other works 3 have found that the increase in the diameter of the central injector will increase the thickness of the vortex cores and strengthens the axial flow velocity thus the vortex breakdown is shifted downstream producing better flame stability. Another groups 13 investigated two types of fuel injection, i.e. axial and trailing.…”
Section: Introductionmentioning
confidence: 99%